2022
DOI: 10.1007/s10006-022-01122-6
|View full text |Cite
|
Sign up to set email alerts
|

Negative-pressure pulmonary edema following maxillofacial surgery: recognize to prevent further complications

Abstract: Negative-pressure pulmonary edema (NPPE) is a rare respiratory complication due to acute upper airway obstruction occurring shortly after extubation. We report a case of NPPE in young adult patient who underwent an eventful general anesthesia. The patient presented laryngospasm followed by acute respiratory distress with pink frothy sputum following. The NPPE was initially misdiagnosed and a preventable tracheostomy was performed. NPPE was managed with mechanical ventilation and diuretics and the patient had f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Diuretics and steroids are often used as adjunctive agents in the treatment of cardiogenic pulmonary edema to promote fluid clearance ( 54 , 55 ). However, the use of some diuretics, such as furosemide, is controversial ( 56 ). Some studies suggested that diuretics are only useful in patients with ARDS and their effect in other patients is limited ( 1 , 4 , 45 ).…”
Section: Treatmentsmentioning
confidence: 99%
“…Diuretics and steroids are often used as adjunctive agents in the treatment of cardiogenic pulmonary edema to promote fluid clearance ( 54 , 55 ). However, the use of some diuretics, such as furosemide, is controversial ( 56 ). Some studies suggested that diuretics are only useful in patients with ARDS and their effect in other patients is limited ( 1 , 4 , 45 ).…”
Section: Treatmentsmentioning
confidence: 99%